2014
DOI: 10.1128/aac.03238-14
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Roles of Major Peptidoglycan Recycling Enzymes in β-Lactamase Production in Shewanella oneidensis

Abstract: c ␤-Lactam antibiotics were the earliest discovered and are the most widely used group of antibiotics that work by inactivating penicillin-binding proteins to inhibit peptidoglycan biosynthesis. As one of the most efficient defense strategies, many bacteria produce ␤-lactam-degrading enzymes, ␤-lactamases, whose biochemical functions and regulation have been extensively studied. A signal transduction pathway for ␤-lactamase induction by ␤-lactam antibiotics, consisting of the major peptidoglycan recycling enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 49 publications
0
31
1
Order By: Relevance
“…However, a homologue of AmpR is absent in S. oneidensis, and the impacts of major peptidoglycan recycling enzymes on blaA expression are distinct from the ampR-ampC paradigm. In particular, the loss of AmpG increases blaA expression, in contrast to the effect observed in previously studied cases (41).…”
contrasting
confidence: 52%
See 4 more Smart Citations
“…However, a homologue of AmpR is absent in S. oneidensis, and the impacts of major peptidoglycan recycling enzymes on blaA expression are distinct from the ampR-ampC paradigm. In particular, the loss of AmpG increases blaA expression, in contrast to the effect observed in previously studied cases (41).…”
contrasting
confidence: 52%
“…We have previously shown that expression of the blaA gene is substantially induced by AMP at high (Ͼ12.5 g/ml) but not low (Ͻ5 g/ml) levels in S. oneidensis (39,41). We speculated that an S. oneidensis strain harboring the E. coli lacZ gene under the control of the blaA promoter would form white and blue colonies on X-Gal plates in the presence of AMP at different levels.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations